Psychosocial risk profiles to address future health emergencies: a country study during the COVID-19 lockdown period in Colombia - Bautista-Gomez, Martha Milena; Millán De Lange, Anthony Constant; Palacio Sañudo, Jorge Enrique; Zuluaga, Laura Sofia; Bolívar Pimiento, Daniel Alfonso; Toloza Perez, Yesith Guillermo; Malagon-Rojas, Jeadran; Mercado-Reyes, Marcela Maria; Ospina, Martha (Frontiers in Public Health, 2024)
Introduction The different strategies used worldwide to curb the COVID-19 pandemic between 2020 and 2021 had a negative psychosocial impact, which was disproportionately higher for socially and economically vulnerable groups. This article seeks to identify the psychosocial impact of the confinement period during the COVID-19 pandemic for the Colombian population by identifying profiles that predict the levels of different mental health indicators (feelings of fear, positive emotions or feelings during free time, and work impact) and based on them, characterize the risk factors and protection that allows us to propose guidelines for prevention or recovery from future health emergencies. Methods This is an observational, cross-sectional, retrospective ex post facto study. Multistage cluster probabilistic sampling and binary logistic regression analysis were used to predict extreme levels of various mental health indicators based on psychosocial indicators of the COVID-19 confinement period and to identify risk and protection factors, Results A relationship was established between the combination of some of the different psychosocial factors evaluated (this combination being the predictive profile identified) with each of the three main variables: feeling of fear (n = 8,247; R = 0.32; p = 0.00; Poverall = 62.4%; 𝜔overall = 0.25; 1-𝛽overall = 1.00), positive emotions or feelings during free time (n = 6,853; R = 0.25; p = 0.00; Poverall = 59.1%; 𝜔overall = 0.18; 1-𝛽overall = 1.00) and labour impact (n = 4,573; R = 0.47; p = 0.63; Poverall = 70.4%; 𝜔overall = 0.41; 1-𝛽overall = 1.00), with social vulnerability determined by sociodemographic factors that were common in all profiles (sex, age, ethnicity and socioeconomic level) and conditions associated with job insecurity (unemployed, loss of health insurance and significant changes to job’s requirements) and place of residence (city). Conclusion For future health emergencies, it is necessary to (i) mitigate the socio-employment impact from emergency containment measures in a scaled and differentiated manner at the local level, (ii) propose prevention and recovery actions through psychosocial and mental health care accessible to the entire population, especially vulnerable groups, (iii) Design and implement work, educational and recreational adaptation programs that can be integrated into confinement processes.